Nearpod as a tool for increasing students’ motivation for learning chemistry - Aleksandra Naumoska; Katerina Rusevska; Aleksandra Blazhevska; Marina Stojanovska (International Journal of Education and Learning, 2022)
The Nearpod software application was implemented in chemistry teaching, thus keeping in touch with current technology appropriate for its use in the education. This is the first study in our country focusing on the usage of the Nearpod as an e-module-based learning media aimed to increasing students’ motivation in chemistry classes, through their engagement during the lesson and active participation. The total sample consisted of 244 9th grade students and 7 teachers from 7 primary schools. This research was based on data collection by modified SMTSL and IMI questionnaires and individual interviews with students and teachers. The data were analyzed and the mean, standard deviation and Cronbach’ alpha reliability coefficient were calculated, which revealed acceptable internal consistency for all subscales. Data obtained from the APQ-N instrument showed that most of the students found this activity enjoyable and interesting, and felt that it was important for their success and progress, but it also enabled them to achieve better results and improve their attention during the online classes. SMTSL-N questionnaire revealed that the students had medium motivation toward chemistry leaning overall. Independent t-tests results stated that there is no significant difference between male and female students’ mean scores. The results obtained in this study, including the interview data as well, indicated that Nearpod-based activities positively influenced students’ motivation in learning chemistry. Nearpod has a great potential to be applied during the face-to-face teaching as a hybrid model in the future, thus making teaching more interesting and less monotonous.